Upaya Pencegahan Tindak Pidana Pencucian Uang Dalam Bentuk Uang Kripto (Bitcoin) Menggunakan Prinsip Kehati-Hatian Perbankan - Anton Jaksa Trisakti; Eko Soponyono (JURNAL BELO, 2021)
The use of virtual money in society became phenomenal when cryptocurrency emerged as a form of technological development in electronic transactions. Bitcoin as a form of cryptocurrency is now in great demand because it is often considered as a potential new investment instrument in maximizing profits. As a result of these developments, bitcoin abuse is a means of money laundering, such as in the corruption case of PT Asabri (Persero) where the perpetrators launder money by means of bitcoin. Given that the legal arrangements regarding Bitcoin in Indonesia are still very limited and have not yet set up prevention efforts, it is necessary to take efforts to prevent money laundering crimes by means of bitcoin. The purpose of this paper is to see how Bitcoin is set up in Indonesia and discover how to prevent money laundering crimes by means of bitcoin. The method of writing juridical normative with conceptual approach. From this research it was found that the regulation on bitcoin in Indonesia has existed so that the legality of bitcoin in Indonesia has been legal, but the use of bitcoin in Indonesia is only limited to trading commodities in futures exchanges in accordance with Regulation of the Minister of Trade No. 99 of 2018 concerning the Implementation of Crypto Asset Trading. Then efforts to prevent criminal laundering by means of crypto money or bitcoin can be done by crypto asset merchant institutions that register their institutions into futures exchanges must use the principle of banking prudence, namely the application of the principle of knowing nasbah, customer due diligence and enhanced due diligence which is then carried out monitoring of service users. The application of the principle is as a commitment in the anti-money laundering program that can be applied in crypto asset trading institusion.